ABOUT INTERRELATION OF THERMAL-KINETIC CHARACTERISTICS OF NUCLEATION, ELECTRONIC COMPOSITION OF THE ALLOY COMPONENTS AND HEREDITY - V. F. Sobolev; O. I. Chichko (Литьë и металлургия, 2004)
The correlation of electrons number on the outside atoms shell of alloying elements and energy of alloy activation, calculated on the basis of Kolmogorsk model of crystallization, is shown. The data is analyzed on the basis of electronic model of donor-acceptor interaction of atoms and fact of heredity of cast alloys.